Implementation of the Light Sitting Meditation Technique in Forming Self-Regulation Skills in Grade IV Students of Elementary School - Saparudin Saparudin; Syarwani Ahmad; Heri Setyo Nugroho (Journal of Social Work and Science Education, 2027)
This research examines the implementation of the silent sitting light meditation technique, its effects on students' self-regulation development, the teacher's role, and the supporting and inhibiting factors in its implementation at SD Tunas Teladan Palembang. A qualitative approach with a descriptive method was employed. Research subjects included fourth-grade students, classroom teachers, and school stakeholders involved in the learning process. Data were collected through observation, interviews, and documentation. The silent sitting light meditation technique was implemented in a structured manner before learning activities to calm students' minds and improve focus. Following participation, students demonstrated enhanced self-regulation skills, including better emotional control, increased concentration, and more disciplined learning behavior. The teacher played a crucial role as facilitator, guide, and director, creating a conducive classroom atmosphere and providing modeling. Supporting factors included school support, a conducive environment, and student enthusiasm, while inhibiting factors comprised varying concentration levels and limited learning time. This study uniquely documents the application of silent sitting light meditation specifically for self-regulation development among elementary students in an Indonesian school context, an area rarely examined empirically. The technique offers a feasible, low-cost strategy for teachers to integrate into daily classroom routines to enhance students' emotional and behavioral regulation. This research contributes empirical evidence that structured meditation before learning effectively develops self-regulation skills, providing actionable insights for educators and curriculum developers seeking non-cognitive interventions to support elementary students' readiness and engagement in the learning process.